TOKOH EMANSIPASI WANITA ISLAM DI MESIR PADA ABAD KE 19 M - Erasiah Erasiah (Kafa`ah: Journal of Gender Studies, 2014)
Egypt is one of the areas that are already well-known as a bag of pre- Islamic civilization of the world set foot there. That's the right word destined for the territory of the Nile valley civilization heritage of this. People with the name  of  the bag  this  civilization  to  this  day still attached either at one of the area located in North Africa. In Egypt it is born leaders of Islamic thinkers who have ideas that are very brilliant and influential to this day in the Islamic world. Of the many characters  who  have  ideas  that  are  very  brilliant,  then  on  this occasion intends to discuss at length about the emancipation of women leaders in Egypt in the 19th century AD.  Keywords: women and emancipationCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i2.98